2017
DOI: 10.1139/cjc-2016-0621
|View full text |Cite
|
Sign up to set email alerts
|

Cholic acid dimers as invertible amphiphilic pockets: synthesis, molecular modeling, and inclusion studies

Abstract: Two dimers of cholic acid were synthesized through simple covalent linkers. The dimers form invertible molecular pockets in media of different polarity; hydrophobic pockets are formed in water and hydrophilic pockets are formed in organic media. Fluorescence studies show that pockets formed by these dimers can serve as invertible hosts for the hydrophobic guest pyrene and the hydrophilic guest coumarin 343. The molecular pocket also enhances dissolution of the weakly soluble cresol red sodium salt in organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…HRMS m / z : calculated for C 52 H 90 N 3 O 8 + [M + H] + 884.6738, found 884.6722; calculated for [M + Na] + 906.6490, found 906.6542. The 1 H NMR and 13 C NMR spectra were consistent with that reported in the literature …”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…HRMS m / z : calculated for C 52 H 90 N 3 O 8 + [M + H] + 884.6738, found 884.6722; calculated for [M + Na] + 906.6490, found 906.6542. The 1 H NMR and 13 C NMR spectra were consistent with that reported in the literature …”
Section: Methodssupporting
confidence: 89%
“…The specific conformational flexibility by the cholic acid dimer 9a was recently described by Zhu and co-workers by studying the behavior of three guest molecules of different polarity. Using molecular modeling, it was suggested that the molecular conformations and interactions with the guest molecule may depend on the length and the functionality of the linker between the two cholic acid moieties in the dimer …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, the same group investigated the self-assembly of the bis-cholic acid compound and that of an analogous dimer bearing a tertiary amine that was synthesized by reducing the carboxylic functions to hydroxyl groups that were then converted to mesylates, which finally reacted with n -butylamine. The compounds act as invertible amphiphilic pockets, allowing the complexation of hydrophobic molecules in water and of hydrophilic ones in nonpolar solvents …”
Section: Poly- and Bisteroidal Derivatives Of Bssmentioning
confidence: 99%
“…The compounds act as invertible amphiphilic pockets, allowing the complexation of hydrophobic molecules in water and of hydrophilic ones in nonpolar solvents. 90 Yang et al synthesized a novel dimeric derivative characterized by two units of DC, a spacer bearing an amide, and a carboxylic function. 91 The compound in alkaline aqueous solutions forms gels consisting of a randomly oriented network of fibers.…”
Section: Poly-and Bisteroidal Derivatives Of Bssmentioning
confidence: 99%